TSCL-SQL:Two-Stage Curriculum Learning Framework for Text-to-SQL - YIN Feng; CHENG Luyi; WANG Qiuyue; WANG Zhijun; DU Ming; XU Bo (东华大学学报（英文版）, 2023)
TP391.1; Text-to-SQL is the task of translating a natural language query into a structured query language.Existing text-to-SQL approaches focus on improving the model's architecture while ignoring the relationship between queries and table schemas and the differences in difficulty between examples in the dataset.To tackle these challenges,a two-stage curriculum learning framework for text-to-SQL(TSCL-SQL)is proposed in this paper.To exploit the relationship between the queries and the table schemas,a schema identification pre-training task is proposed to make the model choose the correct table schema from a set of candidates for a specific query.To leverage the differences in difficulty between examples,curriculum learning is applied to the text-to-SQL task,accompanied by an automatic curriculum learning solution,including a difficulty scorer and a training scheduler.Experiments show that the framework proposed in this paper is effective.